2003
DOI: 10.1210/jc.2002-021422
|View full text |Cite
|
Sign up to set email alerts
|

RET Codon 634 Mutations in Multiple Endocrine Neoplasia Type 2: Variable Clinical Features and Clinical Outcome

Abstract: Since the establishment of a protocol for molecular analysis of hereditary medullary thyroid carcinoma (MTC) in southern Brazil, in 1997, 17 independent families with RET germline mutation have been identified. Because neither molecular diagnosis nor the pentagastrin test were available before the establishment of this protocol, we had the opportunity to observe a large number of patients in whom the disease has evolved naturally without medical intervention, namely prophylactic thyroidectomy. We observed a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
80
4
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 20 publications
11
80
4
11
Order By: Relevance
“…The most penetrant mutation, which also confers the most aggressive phenotype, was found to be Cys634 Arg [8,10,11]. This feature was further supported by another study, which showed that the patients with Cys634Arg mutation had more distant MTC metastases at the time of diagnosis than those with the Cys634Tyr or Cys634Trp mutations and that the metastases developed earlier in patients with Cys634Arg mutations than in those affected by Cys634Tyr mutation [12]. The very low number of identified cases of families with the Cys634Gly mutation makes it improbable to predict the phenotypic and clinical behavior determined by this mutation, despite the fact that one study has suggested that this unique mutation might be associated with early MTC development and high consecutive risk of lymph nodes dissemination [13].…”
Section: Discussionmentioning
confidence: 85%
“…The most penetrant mutation, which also confers the most aggressive phenotype, was found to be Cys634 Arg [8,10,11]. This feature was further supported by another study, which showed that the patients with Cys634Arg mutation had more distant MTC metastases at the time of diagnosis than those with the Cys634Tyr or Cys634Trp mutations and that the metastases developed earlier in patients with Cys634Arg mutations than in those affected by Cys634Tyr mutation [12]. The very low number of identified cases of families with the Cys634Gly mutation makes it improbable to predict the phenotypic and clinical behavior determined by this mutation, despite the fact that one study has suggested that this unique mutation might be associated with early MTC development and high consecutive risk of lymph nodes dissemination [13].…”
Section: Discussionmentioning
confidence: 85%
“…Specific nucleotide and amino acid exchanges at codon634leads in ligand-independent receptor dimerization and auto-phosphorylation, converting the mutated allele to a dominant transforming gene (Asai et al, 1995), and might have a direct impact on tumor aggressiveness in MEN 2A syndrome (Punales et al, 2003). Previously, it has been clearly suggested that C.G2251A (P.G691S) mutation of the RET is related to the early appearance of symptoms in MEN 2A patients; therefore, it is not oncogenic per se (Borrello et al, 2011), and may consider as a low penetrance gene or genetic modifier that associates with a small to moderate increased risk for developing a MTC (Robledo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several Brazilian studies on MEN2 have been recently published, in which clinical and genetic aspects of MEN2 were extensively reviewed (2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14). All clinical variants of MEN2 have a high penetrance rate for MTC and most (90%) RET mutation carriers will exhibit evidence for MTC during their lifetime (15).…”
mentioning
confidence: 99%
“…Briefly, MEN2A comprises 75% of MEN2 cases and most cases (98%) harbor a RET mutation in exons 10 or 11 (codons 609, 611, 618, 620, 630, and 634). RET variants in codon 634 cause 85% of MEN2A cases, mostly with the Cys634Arg and Cys634Tyr mutations (1,7). Furthermore, FMTC cases comprise 20% of MEN2 patients and most of them (85%) have RET mutations in codons 10 or 11 (1,8,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation